IMPLEMENTASI KEBIJAKAN SEKOLAH DASAR INKLUSI ( Studi Kualitatif Deskriptif pada SD Inklusif di Jakarta Utara) - Hasan Asari; Nurmawati Nurmawati; Muhammad Ruslan (Sekolah Tinggi Agama Islam Al Hidayah, 2014)
This paper will focus on the foundation equation receipt decent education to children who have special needs as well as develop and build self-esteem children with special needs when it comes to the school and met with a wide - range of students. The issue of gender equality in education, which in the past two decades become a central issue, one of which is triggered by the fact of gender discrimination in the education world. Gender issues even just one part of the broader social issues that must be addressed, more - in the context of Islam. In Islam it turns out there is an authoritative source of fundamental values that drive universal equality, not only in the context of gender differences, but also in other social issues. Therefore, Islam strictly prohibits discriminatory attitudes. In contrast Islam encourages equality in various levels. That is one meaning of Islam as a religion rahmatanlil'alamin. Background inclusive education is based on four grounds, namely; philosophical foundation, juridical, pedagogical, and empirical. First philosophical foundation. Philosophical foundation implementation of inclusive education in Indonesia is Pancasila are the five pillars simultaneously ideals - ideals are founded on the basic foundation of what is called national unity or diversity. Thus Inclusive education: education that include learners with special needs to get together with other normal students is appropriate in meeting the needs of today's educational needs. Inclusive education is about the same rights to which every child. Inclusive education is a process to remove the barrier that separates learners with special needs of the learners normal so that they can learn and work together effectively in a school. In addition, the government is expected to implement kebijaka implementation and management of a program of inclusion with friendly service and quality to result in better quality for students with a special participant in the study. Implementation of inclusion policies relating dengaan good that the management of inclusion can work well. Obstacles encountered in the implementation of policies and management penyelnggaraan inclusion operationally related standards. To that end, the government should formulate a policy SD. Inclusion in accordance with the needs of the community. Step - steps to address implementation bottlenecks inclusion policy administration and management to increase and improve learning facilities and infrastructure, providing special anggran maximum inclusion, increase the quality and quantity of teachers in accordance with department inclusions. To be recommended in order to implement the policy administration and management should be the maximum.